PARTISIPASI PEMILIH PEMULA DALAM MENGIMPLEMENTASIKAN HAK WARGA NEGARA DI BIDANG POLITIK - R. Samidi; , Wahyu Jati Kusuma (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
The purpose of this study is to determine the role of new voters in implementing citizen rights in politics, analyze the level of participation of new voters in implementing citizen rights in politics, which contains an in-depth understanding of how new voters are involved in the political process so that it is expected to provide insight into the challenges and opportunities in building democratic participation and provide in-depth basic insights for designing policies that support the active involvement of new voters to strengthen the foundations of community democracy. The research method used is descriptive analytical using a qualitative approach. It is called descriptive research because this study reveals in detail and systematically how the participation of new voters in implementing citizen rights in politics. The results of this study are: The participation of new voters in Kramat District varies greatly where new voters in the election are not uniform and are influenced by various factors, including the level of political education, the influence of the social environment, and the attractiveness of certain candidates or issues. New voters tend to prefer candidates or parties that are considered progressive, relevant, and support issues that are close to their lives, such as education, employment, and the environment. Social media plays a major role in shaping the political preferences of new voters. Effective political campaigns on digital platforms can attract attention and support from this group.